PELAKSANAAN PENUNTUTAN DAN EKSEKUSI PIDANA DENDA PERKARA TINDAK PIDANA MIGAS - Safitri, Winda (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2025)
Crimes and To find out and explain the obstacles faced by Prosecutors in implementing criminal fines for Oil and Gas crimes. This study uses an empirical legal approach. Based on the results of the study, it is known that the implementation of prosecution in Oil and Gas Crimes has been in accordance with the principles of prosecution, namely being charged with violating the provisions of Article 55 of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. In terms of Execution of Criminal Fines in Oil and Gas Crimes, several obstacles often occur. The first problem is the lack of active role of the Prosecutor to remind the defendant to immediately pay the fine imposed on him, the economic factor of the defendant in this case the defendant is unable to pay the fine imposed on him, and the absence of asset treasury in oil and gas crimes. Asset treasury is needed to measure the ability and tracking of the assets of the Oil and Gas convict. There is a need for criminal provisions that regulate that if the defendant does not pay the fine as stated in the judge's decision, the defendant's assets can be confiscated in accordance with the fine imposed.